Reduced intensity transplantation for congenital amegakaryocytic thrombocytopenia: Report of a case and review of the literature. (14th October 2013) - Woods, Gary; Bajwa, Rajinder P. S.; Rose, Melissa J.
Abstract CAMT is a bone marrow failure syndrome that usually presents with isolated thrombocytopenia soon after birth. HSCT is curative, and MAC is associated with increased transplant‐related morbidity and mortality, especially in the unrelated setting. We used a RIC regimen with alemtuzumab, fludarabine, and melphalan in a seven‐month‐old patient with CAMT who underwent a MUD HSCT. The transplant was well tolerated with few complications. Neutrophil and platelet engraftment occurred on day +12 and +29, respectively, and she had 100% donor chimerisms on days +19.